PENGELOLAAN SAMPAH BERBASIS MASYARAKAT (STUDI KASUS : KELURAHAN PLEBURAN KECAMATAN SEMARANG SELATAN, KOTA SEMARANG) - Tyas, Riska Libriyanti Mahayuning; Harsasto, Priyatno; Astrika, Lusia (Journal of Politic and Government Studies, 2013)
In order to reduce the amount of waste that goes to landfill Jatibarang, Semarang City Government appointed Ward Pleburan to implement community-based waste management system. Waste management system requires a connection between the theory of the best waste management, proper legal basis and clear policies that can be handled properly, effectively and efficiently. Not only that, waste management, especially those involving the public, can not be separated from the role of government, the private sector itself. Community-based waste management activities in the Ward Pleburan is expected to empower also open employment opportunities for the surrounding community. The research method used in this study is a qualitative method. The data in this study come from interviews with respondents and the data obtained from these reports, books, journals, magazines, and so on. The data was then compiled with the stages of examining the data obtained from the field, analyzing the data and information and then draw conclusions and verification. Thus generating descriptive data to portray a community-based waste management systems in Ward Pleburan Southern District of Semarang, Semarang City. Based on the research conducted, community-based waste management in Ward Pleburan using the principle of the 3Rs (reduce, reuce, recycle) by involving the community. Government's role as regulator, facilitator and dynamic, the role of the public looks to the participation in this activity, and the role of the private sector can be seen with the financial assistance and infrastructure as a manifestation of their CSR. Community-based waste management in Ward Pleburan not optimal due to unresolved obstacles still facing such difficulties marketing products processed garbage, lack of funds as capital activities, lack of control and supervision of the government, as well as the characteristics of communities that are divided into two groups, namely the middle class which tend to be less participative up because I was busy outside the home and the middle class are more atusias down in this activity because it has more free time at home. Keywords: waste management, community-based, partnerships